Angono Digital Arts Hub - Doros, Johanna Liesl S.; Joson, Gerard Thomas (Quezon City College of Architecture, University of the Philippines Diliman, 2019)
Angono Digital Arts Hub in Angono, Rizal is a commercial facility which introduces digital arts to the Art Capital of the Philippines as a tool to boost tourism and aid in employment generation. Aligning with the vision of the municipality which is to strive in business, art, and tourism, the hub is a merger of spaces which houses activities that link, the three. These spaces are grouped into three zones: Creation zone -- this is an animation studio equipped with resources to meet the international client demands and to upgrade local original animated films. Recreation zone -- These are the spaces which showcase Angono and its art, and this is also where tourists can enjoy digital art. Training zone -- Other than training local talent to adapt to the animation industry, the training zone is where student-level and professional artists can collaborate. Anchored in the Philippine Development Plan 2017-2022, this project was conceived out of the need for animation studios which have the capacity and resources to keep up with the increasing demand for outsourced animation services in the global market.
include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Digital arts facility; Angono Digital Arts Hub -- Rizal -- Philippines